2018
DOI: 10.1016/j.jvs.2018.02.053
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine-1-phosphate receptor 1 regulates neointimal growth in a humanized model for restenosis

Abstract: From these data, we conclude that denudation of IMA specifically induces the expansion of S1PR1-positive cells. Based on the nonrandom distribution of S1PR1-positive cells, we consider the possibility that much like lymphocytes, S1PR1-positive smooth muscle cells also use S1PR1 to recognize the sphingosine-1-phosphate gradient from tissue (low) to plasma (high) and so migrate out of the media toward the intima of the injured IMA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…For example, a human mammary artery was denuded or stented ex vivo and then transplanted to the site of the abdominal aorta of a Rowett nude rat ( 123 ). Proliferating cells of the neointima were found after approximately 7 days ( 124 ), whereas a substantial narrowing of the lumen was reached after approximately 28 days ( 125 ).…”
Section: Humanized Models For Restenosismentioning
confidence: 99%
“…For example, a human mammary artery was denuded or stented ex vivo and then transplanted to the site of the abdominal aorta of a Rowett nude rat ( 123 ). Proliferating cells of the neointima were found after approximately 7 days ( 124 ), whereas a substantial narrowing of the lumen was reached after approximately 28 days ( 125 ).…”
Section: Humanized Models For Restenosismentioning
confidence: 99%
“…Moreover, overexpression of S1PR1 or its pharmacological activation attenuated the promoter activity of the Acta2 gene (which encodes SMA), suggesting that S1PR1 contributes to the suppression of SMC differentiation marker genes, a hallmark of vascular remodeling (14). In vivo, S1PR1 expression was found to be increased in the neointima of different animal models of vascular injury (14)(15)(16)(17) and in the neointima of human lesions identified with instent restenosis (18). In addition, treatment with VPC44116, an S1PR1 antagonist, attenuated neointima formation after acute balloon injury of the rat carotid artery (14).…”
Section: Discussionmentioning
confidence: 99%
“…Wamhoff et al (14) observed that vascular injury induced expression of S1PR1 and S1PR3 but reduced that of S1PR2. Further studies reported higher S1PR1 expression in injured arteries from both animals and humans (16)(17)(18). In addition, overexpression of S1PR1 increased SMC proliferation in culture (13) and enhanced arterial occlusion in vivo (15), while pharmacological inhibition of S1PR1 promoted opposite effects (14).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Wu et al 18 show that resolvin D1 promotes resolution of inflammation and inhibits neointimal hyperplasia. And, Braetz et al 19 show that sphingosine-1-phosphate receptor-1 regulates neointimal hyperplasia and may be another good pharmacological target. These studies all give us hope that our interventions will only continue to improve our clinical care in the future.…”
mentioning
confidence: 99%